SARS-CoV-2 convalescent plasma therapy in pediatric patient after hematopoietic stem cell transplantation. (February 2021) - Balashov, Dmitry; Trakhtman, Pavel; Livshits, Anna; Kovalenko, Irina; Tereshenko, Galina; Solopova, Galina; Petraikina, Elena; Maschan, Alexei; Novichkova, Galina
Abstract: Immunocompromised patients, including HSCT recipients, may have a poor prognosis after contracting COVID-19 due to the absence of a pathogen-specific adaptive immune response. One of the possible options for severe COVID-19 treatment may be the transfusion of hyperimmune SARS-CoV-2 convalescent plasma. A 9-month-old girl with juvenile myelomonocytic leukemia received an HSCT from a haploidentical donor. On day +99, during routine virologic monitoring, SARS-CoV-2 was detected without any clinical symptoms. On day +144, the child developed a polysegmental bilateral viral pneumonia with 60 % damage to the lung tissue and confirm a positive SARS-Cov-2 results in throat swab. The patient was treated with tocilizumab and three doses of fresh frozen plasma obtained from a SARS-CoV-2 convalescent patient. Therapy with tocilizumab and three doses of fresh frozen plasma was well tolerated. In spite of full resolution of the lung lesions, complete elimination of SARS-CoV-2 has not been achieved 4 months after the first detection, which is due to persistence of secondary immunodeficiency after HSCT and the lack of reconstitution of the adaptive immune response. This case represents a demonstration of an atypical course of COVID-19 and the delayed development of lung lesions, which was most likely associated with the features of the patient's immune status after HSCT. SARS-CoV-2 convalescent plasma in combination with other therapeutic approaches is one of the possible curative options for this clinical situation.